Constant rate infusion of tramadol in isoflurane-anesthetized pigs undergoing experimental surgery - Catone, G.; Meligrana, M.; Marino, G.; Vullo, C. (Polish Academy of Sciences Chancellery, 2020)
The purpose of this study was to investigate the effect of tramadol (TM) (2 mg/kg) administered intramuscularly (IM) followed by a constant rate infusion (CRI) of TM (2 mg/kg/h) in pigs. Sixteen pigs undergoing experimental surgery were premedicated IM with a combination of alfaxalone (5 mg/kg) and midazolam (0.5 mg/kg). Anaesthesia was induced with propofol (2 mg/kg) intravenously (IV) and maintained with isoflurane. Pigs were randomly assigned to one of the two following groups: Group 1 (n=8): received a loading dose of TM (2 mg/kg) followed by a CRI of TM (2 mg/kg/h); Group 2 (n=8): a loading dose of TM (2 mg/kg) followed by a CRI of lactated Ringer's solution (2 ml/kg/h). Heart rate (HR), respiratory rate (RR), rectal temperature (RT), haemoglobin oxygen saturation (SpO2), fraction of inspired oxygen (FIO2), end-tidal concentration of isoflurane (FEISO), end-tidal carbon dioxide concentration (FECO2), pH, arterial oxygen partial pressure (PaO2), arterial carbon dioxide partial pressure (PaCO2) and bicarbonate concentration (HCO3-) were recorded immediately after loss of righting reflex (T=0 min) and at 15-min intervals over a period of 60 min. Continuous data were analysed using a repeated- -measure analysis of variance (ANOVA) and a p-value ⟨0.05 was considered significant. HR, RR and FEISO were significantly lower (p⟨0.05) in Group 1 at T30 and T45, which corresponded to the time of the most intense surgical stimulation. The results suggest that the TM infusion minimizes the HR and RR response, slightly reducing isoflurane requirements and determining a superior perioperative analgesia.
Keywords: Analgesics, Opioid; Isoflurane; Swine; analgesia, constant rate infusion, pig, tramadol, experimental surgery; Anesthetics, Inhalation; Injections, Intravenous; Animals; Hypnotics and Sedatives; Female; Anesthesia, General; Injections, Intramuscular; Tramadol; 3. Good health